DOES FINANCIAL DIGITALIZATION, DEBIT, CREDIT, INTEREST RATE, AND EXCHANGE RATE AFFECT MONEY SUPPLY IN INDONESIA - Wijayanti, Feny Gusti; Pasaribu, Esti (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2025)
This research aims to determine how financial digitalization, interest, and exchange rates affect the money supply in Indonesia for the long term and in the short term. The data used in this research is secondary data from the Central Bureau of Statistics (BPS) and Bank Indonesia. The analytical method used in this research is the Error Correction Model (ECM), by determining the degree of confidence of 95 percent. This research indicates that, partially, the e-money, debit, interest rate, and exchange rate variables significantly affect the money supply in the long term. In contrast, debit and exchange rates have a considerable positive effect, while e-money and interest rates have a negative significant impact. In the short term, debit and exchange rate variables positively affect the money supply.